Les coopératives de logement, du socialisme au néo-libéralisme. Le cas de Varsovie et de Bratislava - Aurore Meyfroidt; Lydia Coudroy de Lille (Belgeo)
During the socialist regime, housing cooperatives had developed a major role in urban dwelling supply in Central European countries as Poland or Czechoslovakia. They were home of a vast majority of the population, with the exception of the poorest and the richest. Since 1990 national states however have withdrawn from the housing question, and especially from the cooperative sector which they used to support; housing production is thus almost entirely covered by the private sector. What is happening to housing cooperatives? Under which conditions did they shift to condominiums? Do they manage to maintain or renew an alternative supply to the one offered by developers? This paper focusses upon the differentiated evolution of housing cooperatives in Poland and Slovakia and especially in their respective capital cities where housing markets are deeper exposed to metropolitan processes.